Strengthening of cultural identity in regular basic education - Tesén Arroyo, Jorge (2021)
Considering that cultural identity is the basis for knowing the origins of the community and facing the future withcharacter and conviction, na article has been developed with the aim of conducting a systematic review of the scientific literature on strengthening the cultural identity of Regular Basic Education students. The research is a descriptive review article. The search was carried out in different databases such as Dialnet, Scielo, Redalyc, Latindex, Doaj, Redib, Miar, Open Access Academy, Crossref and Creative Commons. To achieve the study objective, 20 qualitative, quantitative and mixed Spanish research papers were selected after a process of elimination and filtering, the information was processed and systematized using the descriptive analytical method. The results reflect that the strengthening of cultural identity is a fundamental element in the development of the country and it is formed from childhood in the relationship of the family, the educational institution and the community. Itis concluded that the Peruvian educational system does not comply with the strengthening of cultural identity due to the centralist curriculum, noncontextualized planning in line with reality and the presence of teachers with a weak cultural identity, particularly in the high Andean areas. Keywords: Interculturality; plurality; culture; art.